Pengaruh Kompetensi Aparatur Desa, Kejelasan Sasaran Anggaran, Pemanfaatan Teknologi Informasi dan Pengawasan BPD Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Pada Desa Banyu Asin Kecamatan Riau Silip Kabupaten Bangka) - Hilda Agustin Hilda Agustin; Anggraeni Yunita; Wenni Anggita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to examine the influence of village apparatus competence, clarity of budget targets, use of information technology and BPD supervision on village fund management accountability in Banyu Asin Village, Riau Silip District, Bangka Regency. This type of research is quantitative research. The data used in this study is primary data obtained from distributing questionnaires directly to members of Banyu Asin Village institutions related to village fund management. The research sample was determined by saturated sampling method (census) and amounted to 31 people. This study gave the results that the competence of village apparatus, clarity of budget targets, utilization of information technology and supervision of the BPD have a significant positive effect on the accountability of managing village funds.